Black carbon particles in human breast milk: assessing infant’s exposure - Cosemans, Charlotte; Bongaerts, Eva; Vanbrabant, Kenneth; Reimann, Brigitte; Silva, Ana Inês; Tommelein, Eline; Poma, Giulia; Ameloot, Marcel; Nawrot, Tim S.; Plusquin, Michelle (Frontiers in Public Health, 2024)
Background/Aim: Human breast milk is the recommended source of nutrition for infants due to its complex composition and numerous benefits, including a decline in infection rates in childhood and a lower risk of obesity. Hence, it is crucial that environmental pollutants in human breast milk are minimized.Exposure to black carbon (BC) particles has adverse effects on health; therefore, this pilot study investigates the presence of these particles in human breast milk.Methods: BC particles from ambient exposure were measured in eight human breast milk samples using a white light generation under femtosecond illumination. The carbonaceous nature of the particles was confirmed with BC fingerprinting. Ambient air pollution exposures (PM2.5, PM10, and NO2) were estimated using a spatial interpolation model based on the maternal residential address. Spearman rank correlation coefficients were obtained to assess the association between human breast milk's BC load and ambient air pollution exposure.Results: BC particles were found in all human breast milk samples. BC loads in human breast milk were strongly and positively correlated with recent (i.e., one week) maternal residential NO2 (r = 0.79; p = 0.02) exposure and medium-term (i.e., one month) PM2.5 (r = 0.83; p = 0.02) and PM10 (r = 0.93; p = 0.002) exposure.For the first time, we showed the presence of BC particles in human breast milk and found a robust association with ambient air pollution concentrations. Our findings present a pioneering insight into a novel pathway through which combustion-derived air pollution particles can permeate the delicate system of infants.